Investigation of Nonlinear Optical Processes in Mercury Sulfide Quantum Dots - Vyacheslav V. Kim; Ivan A. Shuklov; Alaa A. Mardini; Arturs Bundulis; Andrey I. Zvyagin; Rawda Kholany; Anna A. Lizunova; Jurgis Grube; Anatolijs Sarakovskis; Oleg V. Ovchinnikov; Rashid A. Ganeev (Nanomaterials, 2022)
The authors report the third-harmonic generation, nonlinear refraction, and nonlinear absorption in HgS quantum dot (QD) suspensions and films using the nanosecond and femtosecond pulses. High conversion efficiency (7 × 10−4) towards the third harmonic (TH) of the 900–1700 nm, 150 fs laser in the thin (70 nm) films containing HgS QDs deposited on the glass substrates is obtained. The authors analyze spectral dependencies of the TH, nonlinear refractive indices, and nonlinear absorption coefficients of QDs in the 500–1700 nm range and discuss the relation between the TH process and the low-order nonlinear optical properties of these quantum dots.